BaTiO3-based thermistor hollow fibers prepared using a phase inversion spinning process for energy efficient gas sorption. Issue 3 (March 2022) - Bell, Jon G.; Cavasin, N.; Knorpp, A.J.; Graule, T.; Stuer, M.
Abstract: Positive temperature coefficient of resistivity (PTCR) hollow fibers that exhibit self-regulating heating characteristics have potential applications in temperature-swing adsorption systems (TSA), such as CO2 recovery and drying of compressed air. La-doped BaTiO3 hollow fibers displaying a PTCR effect were produced by phase inverting a casting solution consisting of N-methly-2-Pyrrolidone, polymethyl methacrylate, polyvinylpyrrolidone, BaTiO3, TiO2, and La2 O3 through a spinneret into a coagulating waterbath. This was followed by polymer debinding, high temperature sintering between 1350−1400 °C and annealing in air at 1175 °C to produce hollow fibers of the composition Ba0.9975 La0.0025 TiO3 . Hydrothermal synthesis was implemented to deposit an adsorbent porous zeolite X layer within the hollow fiber lumen, which was confirmed by electron dispersive X-ray spectroscopy and CO2 adsorption at 0 °C. Hence, these materials can be applied to energy efficient TSA gas separation processes. The results are discussed in terms of hollow fiber microstructure, adsorption characteristics and electrical properties.